Kemampuan Literasi Membaca Siswa Program Gerakan Literasi Sekolah: Sebuah Perbandingan - Ramdhani, Marlinda (Jurnal Bahasa Indonesia Prima (BIP), 2024)
The School Literacy Movement (GLS) program has been implemented since 2016, but an overview of this program's real impact and evaluation has never been conducted. This study compares reading literacy skills between grade X students in GLS referral and non-referral schools. This research was conducted using a qualitative approach with a multiple site study research type, namely GLS referral and non-referral schools. This research data was the result of a reading literacy test based on seven aspects of reading literacy assessment according to the standard of the Program for International Student Assessment (PISA). The research was conducted in three stages: directing students in each school to answer the reading literacy test instrument, analyzing the results of students' reading literacy test, and comparing the results of students' reading literacy test. The results showed that the reading literacy skills of referral schools were better than those of non-referral schools, as seen from the reading literacy scores between the two schools.